Upaya Meningkatkan Kompetensi Pedagogik Guru Melalui Supervisi Akademik pada MAN 2 Kota Padang Panjang - Agustamam Agustamam (Ranah Research : Journal of Multidisciplinary Research and Development, 2022)
One of the principal's duties is to carry out academic supervision. The point of academic supervision is to guide teachers in improving the quality of the learning process. The goals of academic supervision are for teachers in carrying out the learning process, prepare syllabi and lesson plans, select learning strategies/methods/techniques, use media and information technology in learning, assess learning processes and outcomes, as well as classroom action research (Module for Academic Supervision, Director General of PMPTK, 2021). Therefore, schools as formal institutions that are expected to produce quality students must be run by educators and education staff who have high professionalism to advance the school. However, based on observations over the past year, it appears that the motivation and professionalism of some teachers tend to be low in teaching assignments. This can be assessed from several things, namely only 50% of teachers are present in class on time during teaching hours, only 30% of teachers use learning media while teaching, only 40% of teachers use varied teaching methods, and only 20% of teachers use appropriate learning strategies. In addition to these problems, based on the learning progress report in the semester I for the 2021/2011 school year, there were around 40% of students in the class whose grades had not yet reached the KKM.